(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2021)
The conventional ciphertext retrieval scheme has a number oftroubles, likelow down retrievalperformance, short of single keyword retrieval method and restriction of single machine resources inconventional single server structural design. At the same time, for searchable encryption, it needs tobalance the data security and retrieval efficiency. In this paper, a multi-keyword parallel cipher textretrieval system based on inverted index is proposed. The system adopts different indexencryption methods to improve the performance of cipher text retrieval